Anilinium 3,4-dihydroxybenzoate - Zhu, Si-Ming (International Union of Crystallography, 2012)
The asymmetric unit of the title salt, C(6)H(8)N(+)·C(7)H(5)O(4) (−), contains two anilinium cations and two 3,4-dihydroxybenzoate anions. An intramoleculer O—H⋯O hydrogen bond occurs in each anion. In the crystal, O—H⋯O and N—H⋯O hydrogen bonds link the cations and anions into a three-dimensional array. The structure is further consolidated by weak C—H⋯O interactions.